Partisipasi Usaha Kecil dalam Pengadaan: Studi Empiris Tender Pekerjaan Konstruksi Pemerintah Provinsi Papua Barat - Aprilia, Rachma; Johantri, Bagas; Sopian, Sopian (Polytechnic of State Finance STAN, 2024)
This study aims to analyze the difference in participation of small businesses in government procurement of goods and services before and after the implementation of a Presidential Regulation Number 12 Year 2021. Based on the theory of set aside policy, it is anticipated that the participation of small businesses will increase by reducing competition with non-small businesses. The research employs a quantitative method using data on construction job tenders in West Papua and applies nonparametric difference tests analysis. The results indicate that there is no significant difference in the average participation of construction job tenders in West Papua before and after the implementation of the Presidential Regulation Number 12 Year 2021. The implication suggests the necessity for additional government policies to enhance the participation of small businesses to achieve the goals of government procurement of goods and services more expeditiously.